Molecular Mechanisms for the Adaptive Switching Between the OAS/RNase L and OASL/RIG-I Pathways in Birds and Mammals - Rong, Enguang; Wang, Xiaoxue; Chen, Hualan; Yang, Chenghuai; Hu, Jiaxiang; Liu, Wenjie; Wang, Zeng; Chen, Xiaoyun; Zheng, Haixue; Pu, Juan; Sun, Honglei; Smith, Jacqueline; et al. (Frontiers in Immunology, 2018)
Host cells develop the OAS/RNase L (2-5 oligoadenylate synthetase/ribonuclease L) system to degrade cellular and viral RNA, and/or the OASL/RIG-I (2-5 oligoadenylate synthetase like/retinoic acid inducible protein I) system to enhance RIG-I-mediated IFN induction, thus providing the first line of defense against viral infection. The 2-5 oligoadenylate synthetase like (OASL) protein may activate the OAS/RNase L system using its typical OAS-like domain (OLD) or mimic the K63-linked pUb to enhance antiviral activity of the OASL/RIG-I system using its two tandem ubiquitin-like domains (UBLs). We first describe that divergent avian (duck and ostrich) OASL inhibit the replication of a broad range of RNA viruses by activating and magnifying the OAS/RNase L pathway in a UBL-dependent manner. This is in sharp contrast to mammalian enzymatic OASL, which activates and magnifies the OAS/RNase L pathway in a UBL-independent manner, similar to 2-5 oligoadenylate synthetase 1 (OAS1). We further show that both avian and mammalian OASL can reversibly exchange to activate and magnify the OAS/RNase L and OASL/RIG-I system by introducing only three key residues, suggesting that ancient OASL possess 2-5A activity and has functionally switched to the OASL/RIG-I pathway recently. Our findings indicate the molecular mechanisms involved in the switching of avian and mammalian OASL molecules to activate and enhance the OAS/RNase L and OASL/RIG-I pathways in response to infection by RNA viruses.